Analisis Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah Pada Kota Depok - Sephia Surya Utami, Andini; Sukathen, Fauzy Putra; Noorend, Fariz Maulana; Al Hafizh, M. Reza; Yusdiman, Wawang; Saridawati, Saridawati (Antartika Media Indonesia, 2024)
Anggaran Pendapatan dan Belanja Daerah atau APBD adalah perencanaan keuangan yang dibuat oleh pemerintah daerah bersama DPRD. Secara periodik, APBD dibuat berkala setiap tahun. APBD berisikan program kerja dan rencana kegiatan yang disusun bersama menyesuaikan dengan Rencana Pembangunan Menengah Daerah (RPJMD). Dalam melaksanakan APBD, Pemerintah harus mengoptimalkan penggunaannya dengan tujuan utama adalah mencapai kesejahteraan masyarakat daerah. Dalam artikel ini, kami akan membahas tentang APBD Kota Depok untuk periode 2020 – 2022 yang datanya didapat dari Laporan Realisasi Anggaran Pendapatan dan Belanja Daerah Kota Depok. The Regional Revenue and Expenditure Budget or APBD is a financial plan made by the local government together with the Regional People's Representative Council (DPRD). Periodically, the APBD is prepared annually. The APBD contains Work Programs and Activity Plans that are jointly formulated in accordance with the Regional Medium-Term Development Plan (RPJMD). In implementing the APBD, the Government must optimize its use with the main goal of achieving the welfare of the local community. Changes in the realization of regional revenue and expenditure budgets, both increases and decreases, can be evaluated using revenue variance analysis, revenue growth variance analysis, original regional revenue effectiveness ratio, expenditure variance, expenditure growth analysis, and expenditure efficiency ratio. In this article, we will discuss the APBD of Depok City for the period 2020 - 2022, with data obtained from the Report on the Realization of Regional Revenue and Expenditure Budget of Depok City..